Cooperative Unit Systems: 2. Organizational Strategies - Alyssa Schortinghouse (EDIS)
This 8-page document introduces the core requirements and organizational considerations for replicating a cooperative animal unit. Written by Alyssa Schortinghouse, and published by the UF/IFAS 4-H Youth Development Department, August 2020.